Mereposisi Hubungan Agama dan Negara di Indonesia dalam Perspektif Iman Kristen - Osian Orjumi Moru (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2020)
The relationship between religion and state must be seen in terms of constructive and contextual relations. This means that the relationship between religion and the state is built on the basis of a common vision to create complete human life. This article is qualitative research literature using a descriptive analysis method about the political and national situation in Indonesia as a context for finding the relationship between religion and the state. Religion and the state are both servants of God in bringing prosperity and justice to all humanity. This framework of thinking has logical consequences in repositioning the relationship between religion and the state in a more inductive form based on historical facts and social realities of society. In the end, placing Pancasila as an empirical reality of Indonesian society was formed in the process of the nation's history. Pancasila was formed as an effort based on the common awareness of all components of the nation to harmonize religious values and national values that are different in the Indonesian-Indonesian framework. Abstrak Hubungan antara agama dan negara harus dilihat dalam kerangka hubungan yang konstruktif dan kontekstual. Hal ini berarti hubungan antara agama dan negara dibangun berdasarkan pada kesamaan visi untuk menciptakan kehidupan manusia yang seutuhnya. Artikel ini merupakan sebuah penelitian kualitatif literatur dengan menggunakan metode analisis deskriptif tentang keadaan politik dan nasional Indonesia sebagai konteks untuk mencari hubungan antara agama dan negara. Agama dan negara adalah sama-sama hamba Tuhan dalam mewujudkan kesejahteraan dan keadilan atas seluruh umat manusia. Kerangka berpikir tersebut membawa konsekuensi logis dalam mereposisi hubungan antara agama dan negara ke dalam bentuk yang lebih induktif berdasarkan fakta sejarah dan realita sosial masyarakat. Pada akhirnya menempatkan Pancasila sebagai suatu realita empiris masyarakat Indonesia yang dibentuk dalam proses perjalanan sejarah bangsa. Pancasila dibentuk sebagai upaya berdasarkan kesadaran bersama seluruh komponen bangsa untuk mengharmonisasikan nilai-nilai agama dan nilai-nilai kebangsaan yang berbeda-beda dalam kerangka keindonesiaan.